2004
DOI: 10.1007/s00256-003-0703-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of anterior iliopsoas impingement in total hip replacement

Abstract: Iliopsoas impingement syndrome, an infrequent complication of total hip replacement, has been rarely reported in the radiological literature. It follows chronic friction of the posterior aspect of the iliopsoas muscle and tendon against the acetabular cup, a piece of cement, or cup fixation screws. Clinical findings are non-specific and an imaging modality is required to diagnose the condition. Computed tomography (CT) is considered the gold standard imaging modality in evaluating iliopsoas impingement. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 9 publications
1
39
0
2
Order By: Relevance
“…Sonography can also be used to compare the symptomatic tendon with the contralateral, asymptomatic tendon, although this was not done in our 2 cases. Rezig et al 5 reported a normal appearance of the iliopsoas tendon adjacent to the implant in their patient's contralateral asymptomatic hip.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sonography can also be used to compare the symptomatic tendon with the contralateral, asymptomatic tendon, although this was not done in our 2 cases. Rezig et al 5 reported a normal appearance of the iliopsoas tendon adjacent to the implant in their patient's contralateral asymptomatic hip.…”
Section: Discussionmentioning
confidence: 93%
“…2 The diagnosis of tendinopathy due to impingement has also been made using fluoroscopically guided arthrography and bursography, which have demonstrated a bursa deep to the iliopsoas tendon extending into the pelvis. 3 Rezig et al 5 reported the sonographic appearance of a case of iliopsoas tendinopathy due to acetabular impingement. In that report, the anterior aspect of the acetabular cup protruded beyond the bony acetabular rim; a hypoechoic region corresponding to edema was adjacent to the echogenic protruding portion of the cup, the swollen iliopsoas muscle had a heterogeneous echotexture, and the appearance of the tendon was irregular and indistinct.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the iliopsoas bursa and tendon can potentially be irritated by a prominent anterior edge of the acetabular component, which may exceed the margins of the native acetabulum or be malpositioned (lateral with increased offset or decreased anteversion) [4]. Additional causes of pain related to the acetabular component include fixation screws protruding through the ilium and into the iliacus muscle or extruded cement debris around the anterior rim of the cup [4,5,21]. Characteristically, patients have a brief pain-free postoperative period of several months before experiencing an insidious onset of groin pain during active hip flexion, passive hip extension, and external rotation [5,12,24].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography (Rezig et al 2004, Wank et al 2004, bursography (Cheung et al 2004), and MRI can all reveal bursitis, whereas CT is considered to be the optimal imaging modality as it highlights the impingement zone (Cyteval et al 2003). Therapeutic attitudes regarding the syndrome have ranged from simple negligence, since symptoms sometimes disappear spontaneously, to surgical revision by iliopsoas tenotomy or even replacement of the prosthetic cup.…”
mentioning
confidence: 99%